The Rights-Based Approach to Extractive Resource Governance in Nigeria through the Lens of the UN Guiding Principles on Business and Human Rights: Lessons from South Africa - Abe, Omogboyega (Department of Commercial Law, 2022)
This thesis examines the prospects and potentials of implementing the United Nations Guiding Principles on Business and Human Rights (GPs), in the extractive industry in Nigeria. It considers the prospects of amending existing laws and strengthening regulatory agencies. At the same time, it explores the option of creating new business and human rights institutional agencies to address corporate and business-related human rights abuse. Using the elements of the rights-based approach, the linkages between human rights and extractive activities are examined. The lack of an effective legal and institutional framework to integrate human rights protections into environmental laws has prevented communities which host extractive projects from realising their human rights. On 16th June 2011, the United Nations Human Rights Council, unanimously endorsed the Guiding Principles on Business and Human Rights which provide guidelines for the state's duty to protect human rights, corporate responsibility to respect human rights and access to remedies for victims of corporate-related human rights violations. The GPs provide a rights based approach to safeguarding extractive resource governance, pertinent to a jurisdiction like Nigeria. Drawing significant lessons from South Africa - due to its proactive legislation imposing human rights compliance on companies - the research examines the potential of implementing the GPs in Nigeria's extractive resource industry. A combination of doctrinal and empirical research is utilised in the examination of the subject matter. A key finding of the research is that a proactive implementation of the GPs will reduce or prevent the harmful exploitation of natural resources, thereby creating a positive extractive resource governance and guaranteeing sustainable development. The critical steps towards implementation would be to integrate the GPs into current laws in a way that does not undermine the social contract, but enhances positive governance within communities. The contribution of the thesis in this respect is the development of a legal and institutional framework through which human rights principles can be integrated into domestic legal regimes in the extractive resource industry in Nigeria so as to guide the implementation of the GPs The rights-based approach adopted in the research provides a pathway for the sustainable development of Nigeria's extractive resources. South Africa is at the forefront of the campaign for a binding business and human rights treaty and its domestic legal regime and judicial activity continue to demonstrate the progressive realisation of human rights. Only credible institutions infused with an in-depth understanding of the socio-economic, cultural and political realities of extractive communities can legislate properly for them and monitor compliance. The GPs present a valuable roadmap for strengthening institutions to ensure that business activities in the extractive industry and beyond are not devoid of pertinent human rights considerations.